Harnessing insights from an activity system – OSCEs past and present expanding future assessments. (2nd January 2021) - Reid, Helen; Gormley, Gerard J.; Dornan, Tim; Johnston, Jennifer L.
Abstract: Objective Structured Clinical Examinations (OSCEs) are a dominant, yet problematic, assessment tool across health professions education (HPE). OSCEs' standardised approach aligns with regulatory accountability, allowing learners to exchange exam success for the right to practice. We offer a sociohistorical account of OSCEs' development to support an interpretation of present assessment practices. OSCEs create tensions. Preparing for OSCE success diverts students away from the complexity of authentic clinical environments. Students will not qualify and will, therefore, be of no use to patients without getting marks providing evidence of competence. Performing in a formulaic and often non patient-centred way is the price to pay for a qualification. Acknowledging the stultifying effect of standardising human behaviour for OSCEs opens up possibilities to release latent energy for change in medical education. In this imagined future, the overall object of education is refocused on patient care.